Preoperative Radiation Performed at a Nonsarcoma Center May Lead to Increased Wound Complications Following Resection in Patients With Soft Tissue Sarcomas. (10th December 2021) - Ellison, Ciani; King, David M.; Neilson, John C.; Wooldridge, Adam; Charlson, John A.; Hackbarth, Donald A.; Johnstone, Candice; Bedi, Meena
Abstract : Objectives: Preoperative radiation therapy (RT) followed by wide-local excision with or without chemotherapy is widely accepted as management for soft tissue sarcomas (STS). Although studies have demonstrated excellent local control with this technique, there can be significant morbidity with the development of wound complications. It has been shown that sarcoma resections performed at a high-volume center lead to improved survival and functional outcomes. It is unclear, however, if radiation performed in a high-volume center leads to improved outcomes especially related to morbidity. The goal of this study was to determine whether preoperative RT performed at an academic cancer center have lower rates of wound complication compared with RT performed in community cancer centers. Materials and Methods: A total of 204 patients with STS were treated with preoperative RT±chemotherapy followed by limb-sparing resection. Of these, 150 patients had preoperative RT performed at an academic sarcoma center. wound complication were defined as those requiring secondary operations or prolonged wound care for 4 months following surgery. Predictors for wound complication were evaluated using a Fisher exact test for univariate analysis and logistic regression for multivariate analysis. Results: The overall incidence of wound complication was 28.3%. Significant predictors for wound complication include tumor location and radiation delivered at a community hospital. The postoperative incidence of wound complication was 21% when the preoperative RT was performed at an academic cancer center versus 39% when performed at a community cancer center ( P =0.009). On multivariate analysis, both tumor location ( P =0.0012, 95% confidence interval: 0.03-0.45, odds ratio: 0.13) and RT performed at a community cancer center ( P =0.02, 95% confidence interval: 1.13-4.48, odds ratio: 2.25) remained significant in correlation with postoperative wound complication. Conclusions: Preoperative RT performed at an academic cancer center led to lower rates of postoperative wound complication. This may support the recommendation that preoperative RT and resection of STS be performed at an experienced sarcoma center.